Comportamento mecânico do concreto reforçado por fibras de açaí - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2016)
The use of composite fibers is a method already used by many years and can also be widely exploited to add benefits to concrete structures. The fibers are made of different materials, diameters and lengths can be used in virtually all types of concrete, including in combination, to meet both different purposes. Today the market find various types of fibers, including natural fibers. Vegetable fibers are abundant and have their use motivated by renewable, biodegradable and their availability at low cost. Often as waste without a specific destination, vegetable fibers end up turning into environmental policy issues. This study aimed to analyze the influence of acai fiber in the strength of concrete compression. Specimens were made with addition of different fiber volume fractions, and three types of systems: concrete with addition of 3% acai fiber concrete with addition of 5% acai fiber and a reference concrete without adding fiber. The mechanical behavior of the samples was evaluated by testing the compressive strength.
Keywords: Açaí; Fibras vegetais; Concreto armado